A clinical decision support tool may help to optimise vedolizumab therapy in Crohn's disease. Issue 5 (22nd December 2019) - Dulai, Parambir S.; Amiot, Aurelien; Peyrin‐Biroulet, Laurent; Jairath, Vipul; Serrero, Melanie; Filippi, Jerome; Singh, Siddharth; Pariente, Benjamin; Loftus, Edward V.; Roblin, Xavier; Kane, Sunanda; Buisson, Anthony; et al.
Summary: Background: A clinical decision support tool (CDST) has been validated for predicting treatment effectiveness of vedolizumab (VDZ) in Crohn's disease. Aim: To assess the utility of this CDST for predicting exposure‐efficacy and disease outcomes. Methods: Using data from three independent datasets (GEMINI, GETAID and VICTORY), we assessed clinical remission rates and measured VDZ exposure, rapidity of onset of action, response to dose optimisation and progression to surgery by CDST‐defined response groups (low, intermediate and high). Results: A linear relationship existed between CDST‐defined groups, measured VDZ exposure, rapidity of onset of action and efficacy in GEMINI through week 52 ( P < 0.001 at all time points across three CDST‐defined groups). In GETAID, CDST predicted differences in clinical remission at week 14 (AUC = 0.68) and rapidity of onset of action ( P = 0.04) between probability groups. The high‐probability patients did not benefit from shortening of infusion intervals, and differences in onset of action between the high‐intermediate and low‐probability groups within GETAID were no longer significant when including low‐probability patients who received a week 10 infusion. CDST predicted a twofold increase in surgery risk over 12 months of VDZ therapy among low‐ to intermediate‐probability vs high‐probability patients (adjusted HR 2.06, 95% CI 1.33‐3.21). Conclusions: We further extended the clinical utility of a previously validated VDZ CDST, which accurately predicts at baseline exposure‐efficacy relationships and rapidity of onset of action and could be used to help identify patients who would most benefit from interval shortening and those most likely to require surgery while on active therapy. Abstract : LINKED CONTENT This article is linked to Verstockt and Ferrante and Dulai papers. To view these articles, visit https://doi.org/10.1111/apt.15634 and https://doi.org/10.1111/apt.15671 .